High-Fat-Diet-Induced Weight Gain Ameliorates Bone Loss without Exacerbating AβPP Processing and Cognition in Female APP/PS1 Mice - Peng, Yunhua; Liu, Jing; Tang, Ying; Liu, Jianshu; Han, Tingting; Han, Shujun; Li, Hua; Hou, Chen; Liu, Jiankang; Long, Jiangang (Frontiers in Cellular Neuroscience, 2014)
Osteoporosis is negatively correlated with body mass, whereas both osteoporosis and weight loss occur at higher incidence during the progression of Alzheimer’s disease (AD) than the age-matched non-dementia individuals. Given that there is no evidence that overweight associated with AD-type cognitive dysfunction, we hypothesized that moderate weight gain might have a protective effect on the bone loss in AD without exacerbating cognitive dysfunction. In the present study, feeding a high-fat-diet (HFD, 45% calorie from fat) to female APP/PS1 transgenic mice, an AD animal model, induced weight gain. The bone mineral density, microarchitecture, and biomechanical properties of the femurs were then evaluated. The results showed that the middle-aged female APP/PS1 transgenic mice were susceptible to osteoporosis of the femoral bones and that weight gain significantly enhanced bone mass and mechanical properties. Notably, HFD was not detrimental to brain insulin signaling and AβPP processing, as well as to exploration ability and working, learning and memory performance of the transgenic mice measured by T maze and water maze, compared with the mice fed a normal fat diet (10% calorie from fat). In addition, the circulating levels of leptin but not estradiol were remarkably elevated in HFD-treated mice. These results suggest that a body weight gain induced by the HFD feeding regimen significantly improved bone mass in female APP/PS1 mice with no detriments to exploration ability and spatial memory, most likely via the action of elevated circulating leptin.